2014
DOI: 10.1590/s1679-62252014000100013
|View full text |Cite
|
Sign up to set email alerts
|

Skin extract from Rhamdia quelen(Siluriformes: Heptapteridae) does not promote stress in conspecifics

Abstract: Chemical communication is widely used in aquatic environments, where visual or auditory signals may not be always effective. Fish of the superorder Ostariophysi are known to display epidermal cells (club cells) that produce and store alarm substances, which are released to the water when the skin is damaged. Responses to alarm substances range widely, between active searches for refuge to a complete stop in any locomotor activity. In this study a large number of binucleated club cells (average density of 11 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Apparently, the silver catfish larvae seek concealment because of their small body size, whereas the juvenile increase their amount of movement probably to avoid predator's odor stimulus. However, when adult silver catfish were exposed to conspecifics alarm cues they remained immobile in the first minutes and then increased swimming activity (Souza-Bastos et al, 2014), as observed in the present study. Furthermore, Rivulus hartii (currently Anablepsoides hartii) and yellow perch also demonstrated significant size-dependent trends in response to heterospecific and conspecific alarm cues, respectively, with smaller individuals exhibiting antipredator responses and larger individuals shifting their behavior to increased levels of activity consistent with a foraging or predatory response (Harvey, Brown, 2004;Elvidge et al, 2010).…”
Section: Discussionsupporting
confidence: 80%
“…Apparently, the silver catfish larvae seek concealment because of their small body size, whereas the juvenile increase their amount of movement probably to avoid predator's odor stimulus. However, when adult silver catfish were exposed to conspecifics alarm cues they remained immobile in the first minutes and then increased swimming activity (Souza-Bastos et al, 2014), as observed in the present study. Furthermore, Rivulus hartii (currently Anablepsoides hartii) and yellow perch also demonstrated significant size-dependent trends in response to heterospecific and conspecific alarm cues, respectively, with smaller individuals exhibiting antipredator responses and larger individuals shifting their behavior to increased levels of activity consistent with a foraging or predatory response (Harvey, Brown, 2004;Elvidge et al, 2010).…”
Section: Discussionsupporting
confidence: 80%
“…Activation of the primary stress response pathway in reaction to CSE exposure, as seen in medaka, has also been reported in many other species4142435152. There are examples, however, ( Brycon cephalus and Rhamdia quelen ) where conspecific injury elicits an anti-predator behaviour, but cortisol changes are undetectable5354. It is possible that alternate stress response pathways are triggered in some species, or in specific contexts643.…”
Section: Discussionmentioning
confidence: 85%
“…Sacciform cells have been described as “alarm cells,” with similar morphology and content as club cells, since the presence of these cells and their secretions is thought to serve as signals to other fish to alert them of danger (Bryer, Mirza, & Chivers, 2001; Commens & Mathis, 1999; Smith, 1992; Souza‐Bastos et al, 2014). Sacciform cells described in the present study are located on the superficial layer of the epidermis and discharge their contents directly on the tissue surface, thus differentiating them from club cells, which are usually present in the middle layers of the epidermis and release their contents upon epidermal injury (Elliott, 2011).…”
Section: Discussionmentioning
confidence: 99%